(untitled) (Research, Society and Development, 2023)
Objective: To gather knowledge of the literature on illegal abortion in the context of accessible primary care and the role of the nurse in front of the narrative. Methodology: A descriptive literature review was carried out, with a qualitative character, with materials found on the Virtual Health Library (VHL) and Google Scholar platforms, such as: Scientific journal health and technology - Recisatec , Latin American and Caribbean Literature in Health Sciences (LILACS) and Virtual Nursing Library (BDENF), Scientific Electronic Library Online (SciElO) as well as the technical standard of the Ministry of Health. After searching and applying the inclusion and exclusion criteria, a total of 16 were selected. articles, published between the years 2012 and 2022 written in Portuguese. Results and Discussion: The present work aims to collect, score and present data on the relevance of nursing professional assistance in primary care in situations of abortion, as well as the importance of reception and post development. Illegal abortion is a public health problem that must be discussed without public discernment. It was observed that nursing has an indispensable role in what concerns women who committed illegal abortion, ethically, providing women with assistance and comprehensive care without discrimination. Nursing must be based on principles of humanization, equity and legality. Conclusion: Nurses have an essential role in reducing the risks associated with illegal abortion, in view of the high mortality rate of women who have had illegal abortions.